Improving growth in preterm infants through nutrition: a practical overview - De Rose, Domenico Umberto; Maggiora, Elena; Maiocco, Giulia; Morniroli, Daniela; Vizzari, Giulia; Tiraferri, Valentina; Coscia, Alessandra; Cresi, Francesco; Dotta, Andrea; Salvatori, Guglielmo; Giannì, Maria Lorella (Frontiers in Nutrition, 2024)
The primary purpose of this practical overview is to provide a practical update on appropriate nutritional strategies to improve growth in preterm infants. Current recommendations for improving preterm growth concern both macronutrients and micronutrients, with tailored nutrition since the first days of life, particularly when fetal growth restriction has been reported. Human milk is undoubtedly the best nutrition for all newborns, but, in some populations, if not adequately fortified, it does not adequately support their growth. In all preterms, growth should be correctly monitored weekly to intercept a negative trend of growth and implement nutritional strategies to avoid growth restriction.Similarly, growth should be accurately supported and monitored after discharge to improve long-term health consequences.